Mathematical Literacy through Local Wisdom: A Literature Review on Ethnomathematics Representations in Textbooks and Teaching Modules - Bernadus Resi; Oland Nay; Wike Elise; Erwin Bria (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2025)
This study aims to examine the role of ethnomathematics integration in enhancing mathematical literacy and numeracy among elementary school students within the framework of the Merdeka Curriculum. Employing a qualitative approach through a literature review method, this article analyzes thirteen peer-reviewed research studies and scholarly publications published between 2020 and 2025 that focus on ethnomathematics, mathematical literacy, and numeracy. The findings reveal that the ethnomathematical approach—which leverages local cultural contexts as sources of mathematical learning—offers students more contextualized, meaningful, and engaging learning experiences. The application of ethnomathematics has been shown to strengthen students’ conceptual understanding, enhance numeracy competencies, and cultivate positive attitudes toward mathematics. Moreover, its integration aligns with the objectives of the Merdeka Curriculum, which emphasizes context-based learning, the inclusion of local wisdom, and differentiated instruction. The study further highlights the crucial role of teachers in designing instructional materials and strategies that meaningfully connect mathematical concepts with students’ cultural backgrounds. Accordingly, the development of ethnomathematics-based teaching resources and targeted teacher training is strongly recommended to improve the quality of elementary mathematics education in a more inclusive and transformative manner.